Assessing the Impact of Time Spent in Restrictive Housing Confinement on Subsequent Measures of Institutional Adjustment Among Men in Prison - Labrecque, Ryan M. (Criminal justice and behavior, 2019)
Proponents of restrictive housing argue that its use is an effective deterrent of antisocial behavior, while its critics maintain that the setting causes serious psychological damage and increases noncompliance with institutional rules and expectations. Unfortunately, few studies exist that examine the influence of restrictive housing on behavioral outcomes. This investigation adds to this gap in knowledge by assessing the impact of time spent in restrictive housing confinement on subsequent measures of institutional adjustment among men in prison. Logistic regression analyses reveal no statistically significant relationships between the number of days spent in restrictive housing and subsequent measures of institutional misconduct, and uncover a small, but significant, negative relationship with subsequent placement in restrictive housing. The research and policy implications of these results are discussed.